Low-Vacuum Pyrolysis of YBCO Films by Using Fluorine-Free Metal Organic Chemical Deposition - Zhao Yang; Chuanbing Cai; Ningdong Chu; Shuyun Tong; Yuming Lu; Zhiyong Liu (Crystals, 2022)
The preparation of YBCO superconducting films by using metal organic chemical deposition (MOD) involves low-temperature pyrolysis and high-temperature treatment. The former process generally requires the introduction of water vapor and other gases. The study on pyrolysis in a low vacuum environment and non-carrier gas atmosphere has never been reported. In this work, we explored a low vacuum pyrolysis scheme with simple Argon gas decompression and a carrier-free atmosphere. The effects of heating rate on the microstructure of pyrolysis films were investigated, and the high-temperature treatment temperature (Th) was also optimized. Compared with conventional pyrolysis, the present low-vacuum pyrolysis does not employ the flowing dry or wet gases, facilitating the internal gas release during film decomposition. More importantly, the efficiency was greatly improved with reduced pyrolysis time. The obtained film surface is free of CuO particle, which leads to a lower roughness. We also investigated the effect of Th on the final YBCO film texture and superconductivity. As Th increased from 810 °C to 815 °C, the BaCuO2 phase decreased with enhanced c-axis orientation being evident by XRD and Raman spectra. As a result, the critical current density (Jc) increased from 0.38 MA/cm2 to 1.2 MA/cm2 (77 K, self-field).